Optimal Treatments for NSCLC Patients Harboring Primary or Acquired Amplification - Dantong Sun MD; Junyan Tao MD; Weihua Yan MD; Jingjuan Zhu MD; Hai Zhou MD; Yingying Sheng MD; Chaofan Xue MD; Hong Li PhD; Helei Hou MD, PhD (Technology in Cancer Research & Treatment, 2022)
Background : In non-small cell lung cancer (NSCLC) patients harboring MET mutations, MET-tyrosine kinase inhibitors (TKIs) have been proven to achieve a good response. However, the relative efficacy of different therapeutics in primary NSCLC patients with MET amplification and the treatment options for patients harboring acquired MET amplification after the failure of epidermal growth factor receptor (EGFR)-TKIs remain unclear. Methods: In total, 33 patients harboring primary MET amplification and 9 patients harboring acquired MET alterations identified by next-generation sequencing were enrolled. A retrospective analysis was conducted to compare the efficacy of different therapeutics. In addition, studies reporting various treatments for patients harboring MET alterations were included in the meta-analysis. Results: In our cohort of patients harboring primary MET amplification, crizotinib displayed better efficacy than immunotherapy and chemotherapy, as demonstrated both in first-line ( P  = .0378) and second-line treatment regimens ( P  = .0181). The disease control rates for crizotinib, immunotherapy, and chemotherapy were 81.8%, 72.7%, and 63.6%, respectively. In particular, the median progression-free survival (PFS) time after immunotherapy in patients harboring MET amplification and high programed death ligand 1 (PD-L1) expression (>50%) was only 77.5 days. The meta-analysis revealed that the median PFS times after crizotinib and immunotherapy were 4.57 and 2.94 months, respectively. In patients harboring acquired MET amplification, chemotherapy plus bevacizumab had superior efficacy (310.0 days vs 73.5 days, P  = .0360) compared with MET-TKIs ± EGFR-TKIs. Conclusions: Immunotherapy showed a low response in patients harboring MET alterations, even those with concurrent high PD-L1 expression. MET-TKIs might be an optional treatment with worth-expecting efficacy. However, chemotherapy plus bevacizumab could benefit the subpopulation of patients harboring acquired MET amplification after the failure of EGFR-TKIs.